Application of learning outcomes approaches across Europe : a comparative study - (:unkn) unknown (Publications Office of the European Union, 2016)
"This Cedefop reference publication maps and analyses the shift to learning outcomes in education and training policies and practices across Europe. Bringing evidence on the development of national policies from 33 countries, the study examines progress made in recent years (2009 onwards) and attempts to capture the character of political reform at national, institution and local levels. Ten case studies in nine countries produce new empirical evidence on the presence of learning outcomes approaches in the design and delivery of programmes and curricula for teacher education programmes. Based on extensive literature review, interviews conducted with various stakeholders in curriculum policy-making and practice, focus groups and on-site visits, findings show how learning outcomes approaches increasingly feature as catalysts for policy and practical reform, influencing education and training practice. This publication also reveals the diversity of uses of the learning outcomes approaches being applied and highlights the complexity of implementing learning-outcomes-centred policies and developing appropriate strategies at both systemic and subsystemic levels." (Editor, BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; S 2.3 Berufsbildungspolitik; I 2.2 Europa; Lernergebnisorientierung; Lehrerbildung; Berufsbildungssystem; Bildungspolitik; Europa